Effects of aspergillus niger (K8) on nutritive value of rice straws - Jahromi, Mohammad Faseleh; Juan, Boo Liang; Mohamad, Rosfarizan; Goh, Yong Meng; Shokryazdan, Parisa; Ho, Yin Wan (Academic Journals, 2010)
The objective of this study was to evaluate the use of solid state fermentation for the improvement of the quality of rice straw as animal feed. Rice straw was fermented using Aspergillus niger (K8) with and without additional nitrogen source (urea). Cellulose, hemicelluloses, organic matter (OM), dry matter(DM), acid detergent fibre (ADF), neutral detergent fibre (NDF) and acid detergent lignin (ADL) contents of rice straw were determined before and after 10 days of fermentation. Fermentation has significant (P < 0.01) effect on NDF, but not ADF and ADL contents. Addition of urea as nitrogen source significantly reduced (P < 0.01) the NDF and hemicellulose contents of fermented rice straw. Cellulose content of the rice straw was not affected (P > 0.05), but crude protein (CP) increased significantly (P < 0.01) after fermentation. In vitro gas production technique was used to evaluate the effect of the biological treatment on activity of rumen microorganisms. Fermentation of rice straw using A. niger significantly reduced total gas production (P < 0.01), DM disappearance (P < 0.01) and acetate, propionate and total volatile fatty acids (VFA) production (P < 0.05). Results of the present study showed that solid state fermentation of rice straw using A. niger reduced lignocellulose content, but has negative effect on microbial activity in the rumen ecosystem, presumably due to antagonistic activity of A. niger, or other intermediate products from the fermentation, on the rumen microorganisms.